TINGKAH LAKU PENIAGA WANITA MELAYU DALAM TALIAN: SOROTAN LITERATUR DAN TEORI: BEHAVIOUR OF FEMALE MALAY ENTREPRENEURS: LITERATURE REVIEW AND THEORY - Mohd Nawi, Norsafani Maisarah; Mohd Nasir, Nur Yuhanis; Hyun, Kim Keum (Jurnal Pengajian Melayu (JOMAS), 2020)
The development of information and communications technology (ICT) has created new opportunities for sharing and gathering of knowledge in society, especially in the field of business. The conversion of conventional businesses to online entities has also introduced positive changes to the business world, especially for female Malay entrepreneurs. Overall, online businesses utilise the Internet to conduct their activities. This article aimed to discuss the development of literature, be it in the form of research, books or articles, and theories with regards to the factors of involvement, successes, failures, challenges and support schemes available for female Malay entrepreneurs. In this study, document analysis using a literary research approach was conducted. Findings revealed that there is a substantial amount of writing, ideas and discussions produced by both scholars and the government on the issue at hand. Keywords: Literature review, theory, involvement factors, success and failure factors, business challenges, role of support schemes, female Malay entrepreneurs.